Phase Diagrams and Electromechanical Strains in Lead‐Free BNT‐Based Ternary Perovskite Compounds. Issue 11 (24th July 2014) - Bai, Wangfeng; Li, Lingyu; Li, Wei; Shen, Bo; Zhai, Jiwei; Chen, Haydn; Kleebe, H.‐J.
<x xml:space="preserve">Abstract</x> Lead‐free compounds based on perovskite solid solutions in the ternary system (Bi0.5Na0.5)TiO3‐MeNbO3‐SrTiO3 (BNT‐MeNbO3‐ST, Me=K, Na, (K0.5Na0.5)) were fabricated using a conventional solid‐state reaction method. The effect of ST addition to BNT‐MeNbO3 ceramics on the strain behavior, dielectric, ferroelectric, pyroelectric, and piezoelectric properties was systematically investigated to search the lead‐free piezoelectric materials with an excellent actuating performance. The phase diagrams based on the phase transition temperatures were obtained and the relationship between the phase structure and the electrical properties of the BNT‐MeNbO3‐ST system has been clarified. A qualitative correlation between the morphotropic phase boundary (MPB)composition and tolerance factor t in BNT‐based systems has also been established and the present work indicates that the t value corresponding to the formation of MPB located in a quite narrow range and provides a guideline to predict the approximate MPB region quickly for new solid solutions. The Raman‐spectra analysis, macroscopic properties, and temperature‐dependent relationships of both polarization and strain demonstrated that the large strain response for this investigated system originates from a field‐induced relaxor to ferroelectric phase transformation.